Between Utopia and Dystopia: Colonial Ambivalence and Early Modern Perception of Sápmi. Issue 3 (14th December 2016) - Naum, Magdalena
Abstract : The northernmost regions of Fennoscandia attracted attention of travellers and geographers for centuries. These regions were often imagined in ambivalent terms as homelands of evil and dearth or as places of true happiness. From the seventeenth century onwards, Sápmi (Lapland) became a destination of regular exploration undertaken by Swedish and foreign travellers. These travels made it possible to verify, dismiss, or authorize all that what was previously only speculated about, and ultimately led to the construction of new sets of representations. This paper studies the modes of imagining Sápmi in early modern writing, explores how these were intertwined with state programs in the region, and how the rhetoric and ideological underpinnings of the representations authored by the domestic authors differed from the visions of Sápmi produced by contemporaneous foreign travellers.